2016
DOI: 10.1186/s13014-016-0713-8
|View full text |Cite
|
Sign up to set email alerts
|

Suspected recurrence of brain metastases after focused high dose radiotherapy: can [18F]FET- PET overcome diagnostic uncertainties?

Abstract: BackgroundAfter focused high dose radiotherapy of brain metastases, differentiation between tumor recurrence and radiation-induced lesions by conventional MRI is challenging. This study investigates the usefulness of dynamic O-(2-18F-Fluoroethyl)-L-Tyrosine positron emission tomography (18F-FET PET) in patients with MRI-based suspicion of tumor recurrence after focused high dose radiotherapy of brain metastases.MethodsTwenty-two patients with 34 brain metastases (median age 61.9 years) were included. Due to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 23 publications
2
55
0
1
Order By: Relevance
“…7.8) (Ceccon et al, 2016). Similar accuracy (sensitivity of 86% and specificity of 79% using tumor-to-brain ratio maximum, with cutoff of 2.15) has been reported in other fairly large studies ( n = 50), which also showed added value of time–activity curves (sensitivity and specificity increased to 93% and 84% respectively) (Romagna et al, 2016). …”
Section: Caveats To Interpreting Posttreatment Imaging Changessupporting
confidence: 82%
“…7.8) (Ceccon et al, 2016). Similar accuracy (sensitivity of 86% and specificity of 79% using tumor-to-brain ratio maximum, with cutoff of 2.15) has been reported in other fairly large studies ( n = 50), which also showed added value of time–activity curves (sensitivity and specificity increased to 93% and 84% respectively) (Romagna et al, 2016). …”
Section: Caveats To Interpreting Posttreatment Imaging Changessupporting
confidence: 82%
“…For treatment planning, the MRI protocols consisted of T1-weighted ± gadolinium contrast medium, T2-weighted, and fluid-attenuated inversion recovery (FLAIR) sequences, with a slice thickness of 1.0 mm. O-(2-[18 F]fluoroethyl)-1-tyrosine positron emission tomography (FET-PET) was applied with increasing frequency over the course of the treatment, as previously described, but was not part of the standardized management algorithm [9]. Three-dimensional isocentric/conformal noncoplanar treatment planning was routinely chosen to match the tumor volume as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Other PET radiopharmaceuticals besides FDG have also been investigated in the setting of brain metastatic disease with promising results. Radiolabeled amino acids are the most common radiopharmaceuticals used for investigating new and recurrent brain metastasis, distinguishing true progression from pseudo progression, visualizing irradiated brain metastatic lesions, and managing patients for long-term treatment [22,23,24,26,27]. Finally, a cost-effectiveness analysis showed that the utilization of 18F-FET, in addition to MRI, for recurrent brain metastasis after radiotherapy may be cost-effective [26].…”
Section: Discussionmentioning
confidence: 99%